Kamenev-Type Oscillation Criteria for Generalized Second Order Sublinear -Difference Equations - Benevatho Jaison, A.; Khadar Babu, Sk.; Chandrasekar, V. (International Journal of Engineering and Technology, 2018)
By means of Riccati transformation techniques, authors establish some new oscillation criteria for generalized second order nonlinear -difference equation when Â and Â are quotient of odd positive integers.Â Â Â